2020
DOI: 10.1186/s10020-020-00155-5
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA HULC induces the progression of osteosarcoma by regulating the miR-372-3p/HMGB1 signalling axis

Abstract: Background: Osteosarcoma is a malignancy that normally affects children, adolescents, and young adults. Although accumulating evidence has demonstrated the importance of HULC in osteosarcoma, little is reported about its functional roles and molecular mechanisms. Methods: The expression of HULC and miR-372-3p in osteosarcoma tissues was quantified by qRT-PCR. The regulatory roles of HULC and miR-372-3p on cell proliferation, apoptosis, migration and invasion were determined by CCK-8, colony formation, flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…= 71) and as part of the core RS. HULC is a long non‐coding RNA that has been identified as a driver of tumorigenesis in multiple cancers (Yu et al, 2017; Klec et al, 2019; Ghafouri‐Fard et al, 2020), including liver cancer, osteosarcoma, cervical cancer, pancreatic, stomach, and ovarian cancers (Panzitt et al, 2007; Zhang et al, 2016; Chen et al, 2017a; Wang et al, 2020; Li et al, 2020; Lu et al, 2020). HULC expression is a predictor of poor prognosis across multiple cancers (Peng et al, 2014; Jin et al, 2016; Fan et al, 2017; Chen et al, 2017b), and HULC silencing enhanced the effectiveness of chemotherapy in stomach cancer cell lines (Zhang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…= 71) and as part of the core RS. HULC is a long non‐coding RNA that has been identified as a driver of tumorigenesis in multiple cancers (Yu et al, 2017; Klec et al, 2019; Ghafouri‐Fard et al, 2020), including liver cancer, osteosarcoma, cervical cancer, pancreatic, stomach, and ovarian cancers (Panzitt et al, 2007; Zhang et al, 2016; Chen et al, 2017a; Wang et al, 2020; Li et al, 2020; Lu et al, 2020). HULC expression is a predictor of poor prognosis across multiple cancers (Peng et al, 2014; Jin et al, 2016; Fan et al, 2017; Chen et al, 2017b), and HULC silencing enhanced the effectiveness of chemotherapy in stomach cancer cell lines (Zhang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that the administration of sublethal concentrations of piperine disrupted classical events related to TGF-β1 induced-EMT processes, such as morphology changes, phenotypic alterations, increased cell motility and expression of metalloproteinases [66,76]. In order to monitor the effect of piperine on cell motility, we initially used the wound assay, a widely used technique [55,[77][78][79]. The results showed that piperine abrogated the increased cell motility induced by TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…= 71), and as part of the core RS. HULC is a long non-coding RNA that has been identified as a driver of tumorigenesis in multiple cancers [37,38,39], including liver cancer, osteosarcoma, cervical cancer, pancreatic, stomach and ovarian cancers [40,41,42,43,44,45]. HULC expression is a predictor of poor prognosis across multiple cancers [46,47,48,49], and HULC silencing enhanced the effectiveness of chemotherapy in stomach cancer cell lines [44].…”
Section: Novel Melanoma Combinations Detected By Crsomentioning
confidence: 99%